2006
DOI: 10.1152/japplphysiol.01527.2005
|View full text |Cite
|
Sign up to set email alerts
|

Continued divergence in V̇o2 maxof rats artificially selected for running endurance is mediated by greater convective blood O2delivery

Abstract: We previously showed that after seven generations of artificial selection of rats for running capacity, maximal O2 uptake (VO2max) was 12% greater in high-capacity (HCR) than in low-capacity runners (LCR). This difference was due exclusively to a greater O2 uptake and utilization by skeletal muscle of HCR, without differences between lines in convective O2 delivery to muscle by the cardiopulmonary system (QO2max). The present study in generation 15 (G15) female rats tested the hypothesis that continuing improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 42 publications
4
53
0
Order By: Relevance
“…At the 15th generation, high-capacity runners that never exercise trained had 50, 41, and 48%, respectively, higher maximal aerobic capacity, maximal cardiac output, and maximal stoke volume than the untrained, low-capacity runners (43). Using the speculation that the higher aerobic capacity animals were more likely than the lower aerobic capacity to survive in an environment requiring exercise for survival to reproductive age, we speculate that natural selection could have chosen today's genotypes from those most physically fit to survive in the environment during the hundreds to thousands of years that humans have been on Earth.…”
Section: Adaptations In Gene Structure Over Many Generations In Respomentioning
confidence: 89%
“…At the 15th generation, high-capacity runners that never exercise trained had 50, 41, and 48%, respectively, higher maximal aerobic capacity, maximal cardiac output, and maximal stoke volume than the untrained, low-capacity runners (43). Using the speculation that the higher aerobic capacity animals were more likely than the lower aerobic capacity to survive in an environment requiring exercise for survival to reproductive age, we speculate that natural selection could have chosen today's genotypes from those most physically fit to survive in the environment during the hundreds to thousands of years that humans have been on Earth.…”
Section: Adaptations In Gene Structure Over Many Generations In Respomentioning
confidence: 89%
“…Garland, 1998;Hansen et al, 2006) and recent intraspecific empirical studies (e.g. Gonzalez et al, 2006;Chappell et al, 2007;Gębczynski and Konarzewski, 2011) argue that this is not the case. In particular, experimental evolution studies in rodents suggest that interspecific comparisons simply miss the step-wise evolution of aerobic capacity that can be observed at shorter time scales (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This points to step 4 (tissue capillary-to-cell diffusion) as limiting V O2,run in mice selected on V O2,swim and voluntary running (but not in mice selected on BMR, as their V O2,max elicited by exercise and thermogenesis did not differ). This view is further supported by results of studies on rats selected for divergent low-and high-endurance exercise capacity (Henderson et al, 2002;Howlet et al, 2003;Howlet et al, 2009;Gonzales et al, 2006). These studies demonstrated that the first structural and functional responses to selection enabling greater O 2 utilization in the high capacity runner line type were muscle adaptations that improved oxygen extraction, with little difference in O 2 delivery capacity at the level of heart and lungs (Henderson et al, 2002;Howlett et al, 2003).…”
Section: Discussion Possible Limitations To V O2maxmentioning
confidence: 91%
“…However, further selection on low-and high-endurance exercise capacity resulted in substantial differences in pulmonary function (Kirkton et al, 2009) and cardiac output (Gonzales et al, 2006). Howlett et al therefore hypothesized that central factors (cardiovascular and/or pulmonary changes) could also become limiting during V O2,run ).…”
Section: Discussion Possible Limitations To V O2maxmentioning
confidence: 99%
See 1 more Smart Citation